EFEKTIVITAS METODE EVERYONE IS A TEACHER HERE TERHADAP HASIL BELAJAR SEJARAH KEBUDAYAAN ISLAM PESERTA DIDIK KELAS X MA AS'ADIYAH DARUSSALAM BELAWA RAHMAT KABUPATEN PASANGKAYU - Rahim, Abdul; Mustamin; Nengsih, Ratika; Bunyamin, Andi; Subaedah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low learning outcomes of students in Islamic Cultural History (SKI) learning indicate the need for innovative teaching methods that encourage active participation. One of the active learning strategies that can be applied is the Everyone Is a Teacher Here (ETH) method, which provides opportunities for students to act as learning facilitators for their peers. This study aimed to determine the effectiveness of the Everyone Is a Teacher Here method in improving the learning outcomes of Grade X students in Islamic Cultural History at MA As'adiyah Darussalam Belawa Rahmat, Pasangkayu Regency. This research employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest design. The research subjects consisted of 34 Grade X students selected through total sampling. Data were collected using learning achievement tests administered before and after the implementation of the ETH method. The collected data were analyzed using descriptive and inferential statistics, including normality testing and paired sample t-test. The results indicated that students' learning outcomes improved after the implementation of the Everyone Is a Teacher Here method. The average posttest score was higher than the average pretest score, and hypothesis testing showed a significance value of less than 0.05, indicating a statistically significant difference. These findings demonstrate that the Everyone Is a Teacher Here method is effective in improving students' learning outcomes in Islamic Cultural History. Therefore, this method can be recommended as an active learning strategy to enhance student engagement, confidence, and academic achievement.